Thermal, mechanical and tribological properties of polyamide 6 matrix composites containing different carbon nanofillers - Cheng, Henry Kuo Feng (2015)
Polyamide 6 (PA6) matrix composites were prepared by incorporating multiwalled carbon nanotubes (MWCNTs) or by co-incorporating MWCNTs and carbon black (CB) of different contents. The thermal, mechanical and tribological properties of the composites were investigated using thermogravimetric analysis, nano-indentation, ball-on-disc micro-tribological test and micro-scratch test. It was found that a proper carbon filler content in the composites promoted the thermal stability of the composites, but an excessive loading of carbon fillers degraded the thermal stability of the composites. Although the hardness of the composites decreased with increased carbon filler content, the composites filled with mixed MWCNTs and CB had a higher load bearing capacity than the ones without CB. The tribological results indicated that the increased carbon filler content apparently lowered the friction coefficient of the composites due to the lubricating effect of the carbon fillers. It was also observed that the friction coefficients of the PA6-MWCNT-CB composites were consistently higher than those of the PA6-MWCNT composites due to the lower wear resistance of the PA6-MWCNT-CB composites. The scratch resistance of the composites decreased with increased carbon filler content due to the reduced cohesive strength of the composites.